2015
DOI: 10.1038/ncomms7966
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of noncoding RNAs activates the ESR1 locus during breast cancer adaptation

Abstract: Estrogen receptor-α (ER)-positive breast cancer cells undergo hormone-independent proliferation after deprivation of oestrogen, leading to endocrine therapy resistance. Up-regulation of the ER gene (ESR1) is critical for this process, but the underlying mechanisms remain unclear. Here we show that the combination of transcriptome and fluorescence in situ hybridization analyses revealed that oestrogen deprivation induced a cluster of noncoding RNAs that defined a large chromatin domain containing the ESR1 locus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 68 publications
6
88
0
Order By: Relevance
“…The long intergenic non-coding RNA-ROR has been shown to induce epithelial-to-mesenchymal transition and contribute to breast cancer metastasis (44) and to enhance ERα signaling, conferring resistance to tamoxifen (45). A recent study also indicated that a cluster of lncRNAs, termed Eleanors (ESR1 locus enhancing and activating noncoding RNAs) located within the genomic region containing the ESR1 gene can regulate ERα levels through an enhancer function (46). Of note is the fact that the lncRNA SRA1 (steroid receptor RNA activator 1) acted as a coactivator of ERα, and this action depended on the phosphorylation of ERα at Ser118 (47).…”
Section: Discussionmentioning
confidence: 99%
“…The long intergenic non-coding RNA-ROR has been shown to induce epithelial-to-mesenchymal transition and contribute to breast cancer metastasis (44) and to enhance ERα signaling, conferring resistance to tamoxifen (45). A recent study also indicated that a cluster of lncRNAs, termed Eleanors (ESR1 locus enhancing and activating noncoding RNAs) located within the genomic region containing the ESR1 gene can regulate ERα levels through an enhancer function (46). Of note is the fact that the lncRNA SRA1 (steroid receptor RNA activator 1) acted as a coactivator of ERα, and this action depended on the phosphorylation of ERα at Ser118 (47).…”
Section: Discussionmentioning
confidence: 99%
“…These functional studies provide strong evidence for the potential clinical relevance of ESR1 amplification as a mechanism of ERα pathway regulation. One additional study used LTED MCF7 cells to show a change of ESR1 gene status detectable by FISH; however, the FISH signals were RNase-sensitive and no ESR1 copy number increase was detectable by ESR1 qPCR, suggesting that the FISH results may have been due to probe hybridization to abundant RNA [103] . Gene amplifications in human cancers are markers of the tumor's dependence on the encoded protein, and point to a potential target of therapy [18,20,21,[45][46][47]104,105] .…”
Section: Response or Resistancementioning
confidence: 99%
“…Another example includes GAS5 lncRNA, a cell cycle regulator, which is down regulated in breast cancer samples [29]. Some of the candidate lncRNAs that are shown to be aberrantly expressed in breast cancer include H19 [26, 30], aHIF [31], BCYRN1 [32], UCA1 [33], SRA RNA [34], ZFAS1 [35], CCAT2 [36], LSINCT5 [37], NKILA [25], treRNA [20], Eleanors [38] and MALAT1 [3942]. Recent bioinformatics studies have identified several novel lncRNAs, the expression of which is altered in breast cancer patients: some of these have the potential to be used as prognostic markers [4345].…”
Section: Introductionmentioning
confidence: 99%